Pengaruh Corporate Governance, Laverage, Dan Konservatisme Akuntansi Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Di Bei 2019-2021 - Faradilla Mega Maharani; Hwihanus Hwihanus (Jurnal Akuntan Publik, 2024)
This research is to assess how corporate governance, ownership structure, company attributes, leverage, and accounting conservatism together influence tax avoidance in manufacturing companies listed on the IDX from 2019 to 2021. This research uses quantitative techniques by analyzing financial reports.